The Relationship between Homesickness and Learning Motivation of First Year Overseas Students of the Faculty of Health, Universitas Harapan Bangsa Purwokerto - Maharani, Eliana Septi; Apriliyani, Ita; Triana, Noor Yunida (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Homesickness is a feeling of homesickness that is often experienced by overseas students, especially in the first year. This condition can affect psychological conditions and reduce motivation to learn. Overseas students often face challenges adapting to a new environment, which can increase the risk of homesickness. Research conducted by Firdasari et al at Halu Oleo University found a correlation value of r = -0.351 (p value <0.05), which shows the higher the level of homesickness, the lower the learning motivation. This study aims to analyze the relationship between homesickness and learning motivation of first-year overseas students at the Faculty of Health, Harapan Bangsa University Purwokerto. Method: This study used quantitative methods with a correlational design and cross-sectional approach. The sample consisted of 109 first-year overseas students selected through total sampling technique. Data were collected using Homesickness Questionnaire (HQ) adapted by Utami to measure the level of homesickness and Motivated Strategies for Learning Questionnaire (MSLQ) adapted by Afifah to measure learning motivation. Data were analyzed using Spearman's rho two-tailed correlation test. Result: The results showed a significant negative relationship between homesickness and learning motivation in overseas students with a correlation coefficient of r = -0.344 and p-value = 0.000. These results are in line with previous research, showing that the higher the level of homesickness, the lower the student's learning motivation. Conclusion: This research is expected to be a reference for students in order to optimize high learning motivation and manage homesickness wisely by participating in activities such as student and academic organizations.